2020
DOI: 10.3390/jcm9030742
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Role for Levo-Thyroxine for the Treatment of Arterial Erectile Dysfunction? The Clinical Relevance of the Mean Platelet Volume

Abstract: Background: Arterial erectile dysfunction (ED) is an early sign of vascular damage. Rare evidence has been published so far as to whether subclinical hypothyroidism (SCH) affects arterial erectile function. Therefore, the objective of this study was to fill this gap. Methods: Patients with arterial ED and SCH were consecutive enrolled and randomly divided into Group A (n = 20) and Group B (n = 20). Group A was treated with levo-thyroxine (LT4) at the dose of 1 µg/kg/day for six months, whereas patients of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(28 reference statements)
0
2
0
1
Order By: Relevance
“…In particular, in several cross-sectional studies, MPV, a marker of platelet activation, has a statistically significant higher value in patients with SCH compared to euthyroid ones [18][19][20], suggesting a possible prothrombotic effect of elevated thyrotropin (TSH) [18]. Indeed, the association between SCH and coronary artery disease [33][34][35], as well as endothelial dysfunction [36,37], is established, with an increased risk of cardiovascular events and mortality in those with higher TSH levels, particularly in those with a TSH concentration of 10 mIU/L or greater.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in several cross-sectional studies, MPV, a marker of platelet activation, has a statistically significant higher value in patients with SCH compared to euthyroid ones [18][19][20], suggesting a possible prothrombotic effect of elevated thyrotropin (TSH) [18]. Indeed, the association between SCH and coronary artery disease [33][34][35], as well as endothelial dysfunction [36,37], is established, with an increased risk of cardiovascular events and mortality in those with higher TSH levels, particularly in those with a TSH concentration of 10 mIU/L or greater.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that subclinical hypothyroidism can contribute to ED and CVD directly through the reduction of NO and indirectly through the increase in MPV. Accordingly, in a recent study, we have shown how treatment with levothyroxine reduces MPV levels and improves erectile function in patients with subclinical hypothyroidism compared to patients who are not undergoing treatment [53].…”
Section: Limitsmentioning
confidence: 97%
“…Dunque, l'ipotiroidismo subclinico potrebbe inficiare la funzione erettile direttamente riducendo i livelli di NO e indirettamente tramite l'aumento dei livelli di VPM. In effetti il trattamento sostitutivo con levo-tiroxina in pazienti con ipotiroidismo subclinico è stato recentemente associato a un miglioramento della funzione erettile e a una riduzione dei livelli di VPM rispetto a pazienti che non vengono sottoposti a tale trattamento [18].…”
Section: Prospettive Terapeuticheunclassified